Viscous Dissipation and Heat Transfer Effect on MHD Boundary Layer flow past a Wedge of Nano fluid Embedded in a Porous media - et. al., N. Amar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this investigation the steady of laminar magnetohydrodynamic(MHD) heat and mass transfer two dimensional boundary layer nanofluid flow past a wedge embedded in a porous media in the availability of the viscous dissipation, thermophoresis and Brownian motion effects are taken into account. With the assistance of the similarity transformation, the governing partial differential equations (PDE) are transformed into nonlinear ordinary differential equations (ODE). The solution of the problem is solved numerically by using the MATLAB in built package solver bvp4c. The method's accuracy is examined against recently discussed results and outstanding agreement was reached. The impacts of the pertinent flow parameters are examined through graphs and tabular form.